Optimization of bank loan portfolio return Using non-linear mathematical programming (A Case Study) (Journal of Hama University, 2021)
The main objective of the research is to evaluate the effectiveness of using non-linear mathematical programming method in optimization and maximizing the return of the bank loan portfolio through the case study of Bank Al-Sharq, From 2010 to 2018, by using the solvar function in Microsoft Office Excel.The most important results of using non-linear mathematical programming method has contributed to maximizing the return of the bank loan portfolio, compared to the average value of the return before the improvement process.The recommendations are need to rely on scientific foundations adopted by the mathematical programming mechanisms in making investment decisions, especially The process of granting loans, by relying on mathematical programming mechanisms, and taking into account the reciprocal relationship between the rate of return to be achieved and the size of the risk that the bank may be exposed to.